The burden of cystic fibrosis in North Africa - El Makhzen, Nada; Daimi, Houria; Bouguenouch, Laila; Abriel, Hugues (Frontiers in Genetics, 2024)
Background: Over 200 pathogenic variants in the cystic fibrosis transmembrane conductance regulator (CFTR) gene are associated with cystic fibrosis (CF) -the most prevalent autosomal recessive disease globally, the p.Phe508del variant being the most commonly observed.Recent epidemiological studies suggest a higher global prevalence of CF than previously thought. Nevertheless, comprehensive CF data remains extremely scarce among African populations, contributing to a significant information gap within the African healthcare system. Consequently, the underestimation of CF among children from African populations is likely. The goal of this article is to review the pathogenesis of CF and its prevalence in the countries of North Africa.The prevalence of CF in North African countries is likely underestimated due to the complexity of the disease and the lack of a timely, proper clinical and genetic investigation that allows the early identification of CF patients and thus facilitates therapeutic recommendations. Therefore, specific genetic and epidemiological studies on African individuals showing CF symptoms should be conducted to enhance the diagnostic yield of CF in Africa.